5 - ln w = Z-x-2 x-1 =-x + ln( x-1) Then we can get w = c (...

Info iconThis preview shows page 1. Sign up to view the full content.

View Full Document Right Arrow Icon
Suppose you get w 0 + x - 2 x - 1 w = 0 Move the second term on the right hand side, then we get w 0 = - x - 2 x - 1 w divide w on both sides, you will get w 0 w = - x - 2 x - 1 and then integrate it on both sides Z w 0 w = Z - x - 2 x - 1 which is equivalent to
Background image of page 1
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: ln w = Z-x-2 x-1 =-x + ln( x-1) Then we can get w = c ( x-1) e-x integrate it again, we get v = c 1 xe-x + c 2 then plug in to the initial values....
View Full Document

This note was uploaded on 02/14/2012 for the course MATH 334 taught by Professor Dallon during the Fall '08 term at BYU.

Ask a homework question - tutors are online